Sport management principles and applications - Hoye, Russell; Smith, Aaron C.T; Nicholson, Matthew; Stewart, Bob (Sport Management Series, 2018)
Now available in a fully revised and updated fifth edition, Sport Management: Principles and Applications tells you everything you needed to know about the contemporary sport industry. Covering both the professional and nonprofit sectors, and with more international material than any other introductory sport management textbook, it focuses on core management principles and their application in a sporting context, highlighting the unique challenges of a career in sport management. The book Contains useful features throughout, including conceptual overviews, guides to further reading, links to important websites, study questions, and up-to-date case studies showing how theory works in the real world. It covers every core functional area of management, including: strategic planning; financial management; organizational culture and design; human resource management; leadership and governance; marketing and sponsorship; performance management; sport and the media. The fifth edition includes expanded coverage of sport for development, analytics, monitoring and evaluation, ethics, risk management, sport and health, social media, sustainability, and other contemporary management issues. Complemented by a companion website offering additional resources for students and instructors, this is an ideal textbook for first and second year students in sports management degree programs and for business students seeking on overview of applied sport management principles.